Universal quantum Controlled-NOT gate - Siomau, Michael; Fritzsche, Stephan (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2010)
An investigation of an optimal universal unitaryControlled-NOT gate that performs a specificoperation on two unknown states of qubits taken from agreat circle of the Bloch sphere is presented. The deep analogybetween the optimal universal C-NOT gate and the‘equatorial’ quantum cloning machine (QCM) is shown. In addition,possible applications of the universal C-NOT gate arebriefly discussed.
Gesehen am 07.08.2023